Tools for Managing the Integrity of Tourist Volcanic Caves in the Canary Islands Due to Instability Problems - Luis E. Hernández-Gutiérrez; Juan C. Santamarta; Leticia Pacheco; Esther Martín-González; Helena Hernández-Martín; Ramón Xifré; Carlos Calderón-Guerrero (Geosciences)
Natural caves have a great heritage and natural value, which has made them a tourist attraction that contributes positively to the diversification of tourist offerings in Spain. Volcanic caves are a particular type of natural cave, exclusive to the Canary Islands. The tourist management of these caves entails certain peculiarities that do not occur in other types of tourist establishments. The caves are exposed to certain natural hazards that are important to recognize, evaluate, and where appropriate, plan and adopt the necessary measures to guarantee the safety of visitors and workers. The main natural hazard is the structural stability of the cavity, which can affect workers and visitors. Volcanic caves present structural, lithological, and geomechanical singularities that require a specific methodology to study their stability. This study proposes a specific protocol for the early detection and management of instabilities in tourist volcanic caves, in order to help with the proper management of this ecotourism resource. To this end, tools are provided for the recognition, characterization, and geological and geomechanical analysis, classification of the types of instability in volcanic tubes, and geospatial techniques to control the structural stability.